The Genealogy of Teacher and Student in al-Qur'an and Hadith Perspective (A Review of Maudhu'i Interpretation Analysis) - Hasanuddin Hasanuddin; Iskandar Iskandar (Sekolah Tinggi Ilmu Al-Qur'an (STIQ) Amuntai Kalimantan Selatan, 2022)
The teacher is the leading actor in education and essential to forming the student's character. In consequence, teachers in Islamic education are also referred to as ustadz, mu'allim, murabbi, mursyid, mudarris, and muaddib are mean someone carrying out his duties as an educator and figure who is an example and role model. Additionally, the students refer to talib, murid, and muta'allim, which means individuals grow and develop physically, psychologically, socially, and religiously in navigating life, both the world and the hereafter. This study aims to elaborate on the genealogical meaning of teacher and student in the Qur'an and Hadith based on qualitative research with an Islamic literature study approach. This article uses the data analysis technique of maudhu'i interpretation through the word derivation and the relevance of interpretations in various Islamic literature coherently. The result shows that teachers are educators with a noble position in Islam regarding scientific competence followed by characteristics as caretakers, caregivers, and managers aiming to form students' obedience to empirical values. Correspondingly, the student is an individual who is growing and developing physically, psychologically, socially, and religiously. The teacher and student are both burdened with the responsibility to learn and teach science based on empirical values.